Combating corruption in Croatia in the middle ages : an example of Croatian legal documents - the Law Code of Vinodol (1288) and Statute of the Island of Krk/Vrbnik (1388) - Galović, Tomislav, povjesničar (Array, 2019)
The Croatian medieval lands were encompassed by Western European civilization and its culture, language and script, collectively referred to as orbis Latinus, but they were also lands in which there was a notable influence of different legal systems. In this paper, we will discuss combating corruption in Croatia in the Middle Ages: an example of Croatian legal documents – the Law Code of Vinodol (1288) and Statute of the island of Krk (1388). The first part of this paper is a general introduction, which defines history and legal history of Vinodol. The Law Code of Vinodol is in many ways a vital historical source, not only for legal history and linguistics, but also for knowledge of social structures in medieval Vinodol, the organization of the Church, and the ethnographic and cultural heritage. In the second part of this paper the focus will be on the Statute of Krk or Vrbnik, which is chronologicaly the second codex/statute written in the Croatian language and Glagolitic script. It is formally only a century younger than the Law Code, or Codex, of Vinodol from 1288, and was composed in the same year as the Latin-language Statute of Senj.